The effectivenes of Troika/Imf interventions in Eurozone: the case of Greece: directed research - Lazaridis, Ioannis (2022)
The current paper examines and deals with the effects of the alliance of the three institutions known as the informal “Troika” that was created in early 2010toprovide financial aid programs with fiscal adjustments to euro area countries during the 2010-2018 period. The main purpose of the analysis is to provide an overview of the euro crisis with the imbalances between the South and North and whether the contribution of Troika measures to solve that balance of payment crisis in Greece, had an impact in real variables under an empirical approach. Since the interventions operated to correct the imbalances while not affecting the growth and price stability, the author introduces these dimensions in the synthetic control test and tries to measure the effectiveness of the fiscal adjustment programs in Greece in terms of real variables.